High-density amorphous ice: nucleation of nanosized low-density amorphous ice. (21st December 2017) - Tonauer, Christina M; Seidl-Nigsch, Markus; Loerting, Thomas
Abstract: The pressure dependence of the crystallization temperature of different forms of expanded high-density amorphous ice (eHDA) was scrutinized. Crystallization at pressures 0.05–0.30 GPa was followed using volumetry and powder x-ray diffraction. eHDA samples were prepared via isothermal decompression of very high-density amorphous ice at 140 K to different end pressures between 0.07–0.30 GPa (eHDA 0.07–0.3 ). At 0.05–0.17 GPa the crystallization line T x ( p ) of all eHDA variants is the same. At pressures >0.17 GPa, all eHDA samples decompressed to pressures <0.20 GPa exhibit significantly lower T x values than eHDA 0.2 and eHDA 0.3 . We rationalize our findings with the presence of nanoscaled low-density amorphous ice (LDA) seeds that nucleate in eHDA when it is decompressed to pressures <0.20 GPa at 140 K. Below 0.17 GPa, these nanosized LDA domains are latent within the HDA matrix, exhibiting no effect on T x of eHDA <0.2 . Upon heating at pressures ⩾0.17 GPa, these nanosized LDA nuclei transform to ice IX nuclei. They are favored sites for crystallization and, hence, lower T x . By comparing crystallization experiments of bulk LDA with the ones involving nanosized LDA we are able to estimate the Laplace pressure and radius of 0.3–0.8 nm for the nanodomains of LDA. The nucleation of LDA in eHDA revealed here is evidence for the first-order-like nature of the HDA → LDA transition, supporting water's liquid–liquid transition scenarios.